Self-assessment of Competence in Endoscopy: Challenges and Insights. Issue 4 (23rd June 2020) - Scaffidi, Michael A; Khan, Rishad; Grover, Samir C; Gimpaya, Nikko; Walsh, Catharine M
Abstract: Background: Endoscopists use self-assessment to monitor the development and maintenance of their skills. The accuracy of these self-assessments, which reflects how closely one's own rating corresponds to an external rating, is unclear. Methods: In this narrative review, we critically examine the current literature on self-assessment in gastrointestinal endoscopy with the aim of informing training and practice and identifying opportunities to improve the methodological rigor of future studies. Results: In the seven included studies, the evidence regarding self-assessment accuracy was mixed. When stratified by experience level, however, novice endoscopists were least accurate in their self-assessments and tended to overestimate their performance. Studies examining the utility of video-based interventions using observation of expert benchmark performances show promise as a mechanism to improve self-assessment accuracy among novices. Conclusions: Based on the results of this review, we highlight problematic areas, identify opportunities to improve the methodological rigor of future studies on endoscopic self-assessment and outline potential avenues for further exploration.